Texto literário: importante ferramenta no ensino e aperfeiçoamento das práticas de leitura e escrita - FONSECA, Tatyane dos Santos (2023)
This study presents observations about the practices and resources adopted by teachers in the development of essential skills, reading and writing, correlated to the specifically use of the literary text, in the initial grades of lower fundamental education, starting from of the problematic: if teachers work with literary texts exploring their most diverse meanings, enabling the realization of discussions and reflections by the students about them or if they only use them to work on certain grammar contents. As objective of enabling the perception that literary texts are tools of great value in teaching and improving these essential skills. The research was carried out with teachers trained in Pedagogy, in the PARFOR class of 2011, through a open questionnaire. The collected corpus underwent a descriptive analysis. It was found that the starting from the relationship between reading and the teacher, the stimulating resources and the work itself develops, mastering the definition of a literary text interferes with its use as well as the lack of training on this type of text interferes with the resourcefulness of its use in the classroom class, making it impossible to actually take advantage of this resource that is considered pleasant and attractive to students; often not so well enjoyed in the teaching process and development of reading also due to the deficient training received by the teacher. In addition to the 1997 Portuguese Language PCNs, studies by authors such as: Antunes, Bragato, Koch and Elias, Lajolo and Zilberman, Samuel, Santos and Souza